Selective Agonists of Nuclear Retinoic Acid Receptor Gamma Inhibit Growth of HCS‐2/8 Chondrosarcoma Cells. Issue 5 (19th December 2019) - Shield, William P.; Cellini, Ashley; Tian, Hongying; Wilson, Kim; Dan, Yang; Abzug, Joshua M.; Garcia, Sonia; Moritani, Norifumi; Alferiev, Ivan; Chorny, Michael; Takigawa, Masaharu; Ng, Vincent Y.; et al.
ABSTRACT: Chondrosarcoma is the second most common primary bone sarcoma. Treatment of chondrosarcoma is limited to surgery due to radiation and chemotherapy resistance of this cancer. An ideal treatment for chondrosarcoma would be a well‐tolerated, minimally invasive local or systemic treatment modality to halt or slow tumor growth prior to resection of local, unresectable local, or metastatic disease. Palovarotene, an agonist of nuclear retinoic acid receptor γ (RARγ) has shown therapeutic action for treatment of heterotopic ossification and osteochondroma without serious adverse effects in animal models. We hypothesized that selective agonists of RARγ would have an inhibitory effect on chondrosarcoma. All human chondrosarcoma specimens expressed RARγ as determined by immunohistochemical staining. The ΗCS‐2/8 chondrosarcoma cell line, established from low‐grade human chondrosarcoma, was used to examine the actions of RARγ agonists. In ΗCS2/8 pellet cultures, RARγ agonist treatment reduced the mass size and significantly decreased total glycosaminoglycan, protein amounts, and gene expression levels of cartilage matrix molecules when compared with control groups. Systemic treatment with RARγ agonists significantly inhibited the growth of ΗCS‐2/8 cell transplants in vivo. Furthermore, local injection of RARγ agonist‐loaded poly‐lactic acid nanoparticles induced regression of the mass size of the transplants. Histologic analysis demonstrated that RARγ agonist treatment inhibited cell proliferation activity and stimulated encapsulation of the tumor. These findings indicate that RARγ agonists, including palovarotene, may have an anti‐tumor effect on low‐grade chondrosarcomas. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 38:1045‐1051, 2020